Prolactinomas Resistant to Treatment With Dopamine Agonists: Long-Term Follow-Up of Six Cases - Gonzaga, Maria de Fátima de Magalhães; de Castro, Lucas Faria; Naves, Luciana Ansaneli; Mendonça, José Luiz; Oton de Lima, Benicio; Kessler, Iruena; Casulari, Luiz Augusto (Frontiers in Endocrinology, 2018)
Introduction Prolactinomas are preferentially treated with dopamine agonists. However, a few adenomas are resistant to this treatment. Objective To evaluate the characteristics of patients with resistance to dopamine agonists in the long-term. Method A retrospective study of six cases was made. Patients who did not achieve normalized prolactin blood concentrations and a reduction of more than 50% of the tumor volume with the minimum dose of 3.0 mg per week of cabergoline for three months or the maximum supported dose of bromocriptine for six months were considered resistant to dopamine agonists. Patients were followed up at the Clinic of Neurology and Endocrinology or the University Hospital of Brasilia. Results Six patients were selected. Three patients were initially treated with bromocriptine prior to treatment with cabergoline. Four patients were men, and two were women. At the time of diagnosis, ages ranged from 9 to 62 years. Initial prolactin concentrations ranged from 430 to 14,992 ng/mL and in the last assessment ranged from 29.6 to 2,169 ng/mL. The maximum weekly doses of cabergoline ranged from 3.0 to 4.5 mg. Follow-up time ranged from seven to 17 years. Normalization of prolactin concentrations occurred only in one woman after 17 years of treatment. Tumor regression occurred in all patients, but total disappearance of the adenoma with an empty sella occurred in two patients. Three patients also underwent surgery, but only one woman was cured of the disease. Conclusion This study confirms that tumors resistant to dopamine agonists are more aggressive, that long-term treatment with a high dose of cabergoline may reduce the size of the tumor without its disappearance, and that normalization of prolactin concentration rarely occurs.